Head Size and Intelligence Quotient (IQ) in Elementary School Students - Oski Illiandri; Dwi Setyohadi; Aji Ilman Sjidan; Aldiya Jamila; Adwa Humaira; Maulana Malik Ibrahim; Ahmad Rofii (Future Science, 2021)
Superficially, Intelligence is an ability to planning, thinking, talking, rationalization, comparing, and understand with other. One of many methods to rate for intelligence, is Draw-A-Man test, it’s introduced by Goodenough in 1926 to researching children’s creativity, mental age, and visual and motoric intelligence with some code based on picture that the children drawed. The aim of this study was to determine the correlation between head circumference and head length with Intelligence Quotient of the 3rd grade Karang Mekar 1 Banjarmasin elementary school’s student. The methodsof this study used observational analytics with a cross-sectional approach. The sampling technique was total sampling with a sample of 65 students aged 7 to 10 years and fulfilling the inclusion and exclusion criteria. The results of data analysis using the Spearman correlation test showed that the correlation point on the head circumference and head length with IQ were p=0.888 and p=0.985. Based on the results of this study, it can be concluded that there is no significant correlation between the the head circumference and head length with Intelligence Quotien in elementary student.